HUBUNGAN TINGKAT PEMAHAMAN PASIE HUBUNGAN TINGKAT PEMAHAMAN PASIEN TERHADAP PENGGUNAAN ANJUNGAN PENDAFTARAN MANDIRI (APM) DI UNIT RAWAT JALAN RUMAH SAKIT AWAL BROS PANAM: HUBUNGAN TINGKAT PEMAHAMAN PASIEN TERHADAP PENGGUNAAN ANJUNGAN PENDAFTARAN MANDIRI (APM) DI UNIT RAWAT JALAN RUMAH SAKIT AWAL BROS PANAM - Yuliana, Anastasya Shinta; Madona, Helliza; Tonis, Marian; Wulan, Wulan Patricia; Putri Andriani, Desvita; Putri; Destiani , Nur Laili; Putri , Aprilia; Lestari, Resi; Hendriko , Aditya (LPPM Universitas Awal Bros, 2025)
APM is an Independent Registration Platform, which at first glance looks like an ATM machine, which allows general patients and BPJS patients who have been recorded (have had previous treatment at the hospital) to register and receive an SEP letter (Patient Eligibility Letter) without having to go through the registration counter. The purpose of this study was to determine the relationship between the level of patient understanding of the use of self-registration platforms with variables of content, format, accuracy variables, timeliness, and ease of use. This study uses a type of quantitative research with a cross sectional design, which is carried out in the outpatient unit of the Awal Bros Panam Hospital with a total of 100 patient respondents with the Accidental Sampling technique. Data collection using a questionnaire. The results showed that in general, there are still many patients who do not understand the use of self-registration platforms, due to the habit of not reading the provisions and guidelines that have been provided by the hospital and are more likely to need officers than to register independently using a self-registration platform machine, so it is recommended to add educational procedures that are easily understood by patients using local languages and add educational tvs near the self-registration platform machine.